Giant thyroid metastasis originating from renal carcinoma: a case report - Yin, Yu-Ting; Gui, Chao (Frontiers in Oncology, 2025)
Thyroid metastases from clear cell renal cell carcinoma are rare. Although they often present in combination with primary thyroid tumors, they are difficult to distinguish from primary thyroid tumors on imaging and are easily misdiagnosed preoperatively. In this article, we report a case of clear cell renal cell carcinoma that metastasized to the thyroid gland. A 69-year-old woman had been diagnosed with a thyroid mass 8 years earlier, which gradually enlarged into a giant thyroid tumor. Tumor compression of the trachea caused intermittent wheezing, and the tumor protruded into the thoracic cavity. The patient had a history of right nephrectomy performed 17 years prior due to right kidney necrosis. Following the preliminary diagnosis of a thyroid tumor, we performed a total thyroidectomy. Histopathological examination revealed metastatic clear cell renal cell carcinoma. The postoperative recovery was good; the patient did not receive further treatment or show signs of recurrence during the 1-year follow-up period. This case illustrates that thyroid metastasis of clear cell renal cell carcinoma can occur many years later and may be present in conjunction with primary thyroid tumors, making preoperative diagnosis difficult. Thorough surgical excision can provide good treatment results. This case report aims to promote the understanding and diagnosis of thyroid metastasis in patients with clear cell renal cell carcinoma.